Changes in the Body Size of Carabid Beetles Along Elevational Gradients: A Multispecies Study of Between- and Within-Population Variation - Baranovská, Eliška; Tajovský, Karel; Knapp, Michal (Environmental entomology, 2019)
Geographic variation in body size has fascinated biologists since the 19th century as it can provide insight into the evolution of the body size of various organisms. In this study, we investigated body size variation in eight carabid species/subspecies (Coleoptera: Carabidae) along elevational gradients in six Central European mountain ranges. First, we examined elevational variation in body size and whether female and male body sizes differed in their responses to elevation. Second, we examined intrapopulation variation in body size along an elevational gradient, and we compared the degrees of intrapopulation variation between males and females. The investigated species either followed a converse Bergmann's cline (Carabus auronitens auronitens Fabricius 1792; Carabus linnei Panzer 1810; Pterostichus melanarius (Illiger, 1798); Pterostichus pilosus (Host, 1789)) or their size was unaffected by elevation (Carabus auronitens escheri Palliardi, 1825; Carabus sylvestris sylvestris Panzer, 1796; Carabus sylvestris transsylvanicus Dejean, 1826; Pterostichus burmeisteri Heer, 1838). Females were the larger sex in all the investigated species, but the degree of sexual size dimorphism differed between species. In general, the degree of sexual size dimorphism showed no change with elevation. The degree of intrapopulation variation in body size slightly increased with elevation in C. sylvestris sylvestris and P. pilosus. Overall, the intrapopulation variation in body size significantly differed among the investigated carabid species. The existing literature on intrapopulation variation in the body size of insects is limited, but further investigation of this issue could provide a better understanding of the mechanisms that generate geographical clines.
Keywords: Animals; velikost těla; altitudinal gradient; Female; Geography; geographical cline; Coleoptera; ženské pohlaví; brouci; Body Size; zeměpis; Sex Characteristics; intrapopulation variation; Male; hmyz; pohlavní dimorfismus; sexual size dimorphism; converse Bergmann’s rule; zvířata; mužské pohlaví; Insecta